2004
DOI: 10.1103/physreve.70.021902
|View full text |Cite
|
Sign up to set email alerts
|

Lateral organization of cholesterol molecules in lipid-cholesterol assemblies

Abstract: We present results of an off-lattice simulation of a two-component planar system, as a model for lateral organization of cholesterol molecules in lipid-cholesterol assemblies. We explore the existence of "superlattice" structures even in fluid systems, in the absence of an underlying translational long-range order, and study their coupling to hexatic or bond-orientational order. We discuss our results in context of geometric superlattice theories and "condensation complexes" in understanding a variety of exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several theoretical and experimental studies have suggested that sterols (e.g., cholesterol and ergosterol) tend to adopt regular, superlatticelike distributions in lipid bilayers, and PC bilayers in particular. ,, It has been proposed that cholesterol imposes steric strain in the acyl chain matrix, which drives cholesterol molecules toward a regular distribution . The same study provided evidence that some of the putative superlattices have a centered rectangular, rather than hexagonal, symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Several theoretical and experimental studies have suggested that sterols (e.g., cholesterol and ergosterol) tend to adopt regular, superlatticelike distributions in lipid bilayers, and PC bilayers in particular. ,, It has been proposed that cholesterol imposes steric strain in the acyl chain matrix, which drives cholesterol molecules toward a regular distribution . The same study provided evidence that some of the putative superlattices have a centered rectangular, rather than hexagonal, symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported earlier that the miscibility of cholesterol increases significantly in the saturated phosphatidylcholine (PC) lipids in comparison to that in the unsaturated one. Previous reports concerning the PC–cholesterol interaction both in the Langmuir monolayer and in the model bilayer ,, have witnessed the cholesterol-induced structural changes in the phospholipid model membranes. Despite vivid research with model biomembranes, the phospholipid phase dependency of lateral and out-of-plane organization of cholesterols as a function of concentration is still not achieved satisfactorily and needs significant effort to understand the interaction mechanism.…”
Section: Introductionmentioning
confidence: 96%
“…x k G , y k G and φ k G in (16)- (18) are Gaussian random variables with zero mean and unit variance.…”
Section: Appendix: Discretization Of Stochastic Equationsmentioning
confidence: 99%